(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
At the Faculty of Forest Industry, seemingly for the first time in the bandsaw studies history, the statically indeterminate problem of spring mechanism tension in bandsaw blade sections was set up and solved. The solution, transferred and generalized for a horizontal bandsaw, was defended in a Ph.D. thesis. Questions and discussions arose necessitated additions and details to the solution spared in previous papers for their limited volume. Now, the following points are detailed: the concentration of distributed loads, the subcritical friction, and the application of L’Hôpital’s rule for obtaining the tension of the blade in the state of idle running (without cutting).